Effects of a psychotherapeutic group intervention in patients with refractory mesial temporal lobe epilepsy and comorbid psychogenic nonepileptic seizures: A nonrandomized controlled study. (May 2018) - de Barros, Amanda Cristian Serafim; Furlan, Ana Eliza Romano; Marques, Lucia Helena Neves; de Araújo Filho, Gerardo Maria
Highlights: Psychotherapy in PNES improve seizure frequency and psychosocial functioning. Patients with TLE-MTS and PNES were submitted to a psychological intervention. Improvements in levels of alexithymia and anxiety/depression were observed. Improvements in quality of life and reduction of seizure frequency were observed. Abstract: Purpose: Psychogenic nonepileptic seizures (PNES) are paroxysmal episodes superficially resembling epileptic seizures but are not associated with any electrical abnormalities. Despite the existence of recent evidence addressing psychological interventions on PNES, there is a scarcity of studies investigating such interventions on patients with dual diagnoses, such as in temporal lobe epilepsy/mesial temporal sclerosis (TLE-MTS) with comorbid PNES; TLE-MTS is a very frequent epilepsy syndrome found in tertiary centers. We aimed to investigate the effects of a group psychotherapeutic intervention program based on cognitive-behavioral therapy (CBT) on patients dually diagnosed with TLE-MTS and PNES treated in a tertiary center. Method: Patients with TLE-MTS and PNES who were followed-up in a tertiary center were invited. The intervention consisted of eight weekly, semi-structured group meetings. The Brazilian versions of the Quality of Life Scale (SF-36), the Toronto Alexithymia Scale (TAS), the Hamilton Depression Scale (HAM-D), the Hamilton Anxiety Scale (HAM-A), and the Ways of Coping Checklist (WCC) were applied before and after the intervention. Results: Forty-seven patients were enrolled (25 females; 53.2%). Psychiatric disorders (PD) were observed in all 47 patients (100%); Major Depressive Disorder (MDD) was the most frequent PD (24; 51.0%). There were improvements on quality of life ( P  = 0.003), decreased depression ( P <0.0001) and anxiety symptoms ( P  = 0.02), decreased levels of alexithymia ( P  = 0.02) and a reduction in seizure frequency ( P  = 0.02) after the intervention. Conclusions: Present data suggest a positive impact of a group psychological intervention based on CBT in patients with TLE-MTS and PNES, highlighting this therapeutic possibility for this specific subgroup.